Does climate policy exacerbate spatial development inequality? Quasi-experimental evidence from China - Xiaoke Zhu; Weigang Liu; Jian Liu (Sustainable Cities and Society, 2025)
This study aims to examine the causal relationship between climate policy and spatial development inequality within cities. To this end, we leverage the temporal and spatial variations in the implementation of the low-carbon city pilot initiative (LCCPI) to perform a staggered difference-in-difference (DID) estimation. Our estimated results demonstrate that the LCCPI is associated with an approximate 4.4 % reduction in the Gini coefficient for nighttime light intensity. Our findings are robust to alternative measures and different specifications. Further mechanism analyses reveal that the LCCPI operates by narrowing the green innovation gap and improving the factor allocation. Notably, we observe a more pronounced decrease in spatial development inequality in resource-dependent and high-marketization cities.
Keywords: D63; Q01; Q56; R11; 330; climate policy; spatial development inequality; green innovation; factor allocation; staggered DID